Hubungan Self Efficacy dengan Kualitas Hidup Penderita Gagal Ginjal Kronik di Ruang Hemodialisa Rumah Sakit Bhayangkara Setukpa Lemdikpol Kota Sukabumi - Nunung Liawati (Fakultas Kesehatan Universitas Muhammadiyah Sukabumi, 2022)
Chronic Kidney Disease (CKD) is a dangerous non-communicable disease, one of the therapies used is hemodialysis. As the duration of hemodialysis can affect the patient's quality of life. The purpose of this study was to determine the relationship between self-efficacy and quality of life in patients with chronic kidney disease. Chronic kidney disease is defined as a condition where the kidney function is not good, there is an accumulation of metabolic waste products and fluids in the body which results in impaired body function. One of the factors that affect the quality of life is self efficacy. This research uses correlational research with cross sectional approach. The population is 30 people with a sample size of 30 people. The sampling method is using Total Sampling. Statistical analysis using Fisher's exact. The results showed that self-efficacy was good at 60% and good quality of life was 66.7%. There is a relationship between self-efficacy and quality of life in patients with chronic kidney failure because it has a p-value of 0.009. The conclusion of the study is that there is a relationship between self-efficacy and the Quality of Life of Patients with Chronic Kidney Disease in the Hemodialysis Room, Bhayangkara Setukpa Hospital, Lemdikpol, Sukabumi City. It is hoped that the relevant agencies will continue to improve health counseling services about self-efficacy to further improve the quality of life and can minimize the possibility of chronic kidney disease.